2022
DOI: 10.3389/fonc.2022.870544
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Prediction of Malignant Transformation of Sinonasal Inverted Papilloma Using MR Radiomics

Abstract: PurposeAccurate preoperative prediction of the malignant transformation of sinonasal inverted papilloma (IP) is essential for guiding biopsy, planning appropriate surgery and prognosis of patients. We aimed to investigate the value of MRI-based radiomics in discriminating IP from IP-transformed squamous cell carcinomas (IP-SCC).MethodsA total of 236 patients with IP-SCC (n=92) or IP (n=144) were enrolled and divided into a training cohort and a testing cohort. Preoperative MR images including T1-weighted, T2-w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 39 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…Recently, Ramkumar et al (15) found that MRI-based texture analysis had the potential to classify SNIP and squamous cell carcinoma. Another previous study (16) showed that machine learning models based on MRI radiomics and morphological features achieved satisfactory predictive efficiency in differentiating SNIP from SNIP-transformed squamous cell carcinomas. Despite radiomics method has been utilized in prior studies to classify sinonasal tumors (17,18), and has promising performance, the most appropriate sequence and machine learning classifier for model construction remain undetermined.…”
Section: Introductionmentioning
confidence: 95%
“…Recently, Ramkumar et al (15) found that MRI-based texture analysis had the potential to classify SNIP and squamous cell carcinoma. Another previous study (16) showed that machine learning models based on MRI radiomics and morphological features achieved satisfactory predictive efficiency in differentiating SNIP from SNIP-transformed squamous cell carcinomas. Despite radiomics method has been utilized in prior studies to classify sinonasal tumors (17,18), and has promising performance, the most appropriate sequence and machine learning classifier for model construction remain undetermined.…”
Section: Introductionmentioning
confidence: 95%
“…In this field, machine learning (ML) algorithms are used to select the best features and develop and improve models, which have the potential to improve predictive power (8). In the last 2 years, studies regarding artificial intelligence in IP have gradually become a hot topic (9)(10)(11)(12)(13). In one study, Li et al (14) designed a deep learning framework through convolutional neural networks to automatically identify IP and NP with high AUC values of 0.95.…”
Section: Introductionmentioning
confidence: 99%